Pengaruh Stres Kerja terhadap Kinerja Perawat di Instalasi Rawat Inap PMN RS Mata Cicendo - Nanang Tedi; Syamsul Arifin; Farida Gustini (Jurnal Health Sains, 2021)
Based on data on the number of patients treated per year and the number of nurses in the inpatient installation of the National Eye Center of the Cicendo Eye Hospital, Bandung, it shows that there is a shortage of nurses because the number of patients continues to increase which will result in fatigue or too much workload which can cause stress work. This study aims to determine the effect of work stress on the performance of nurses in the inpatient installation of the National Eye Center at Cicendo Eye Hospital, Bandung in 2021.This type of research is quantitative with a cross sectional approach. The sample of this research is 50 nurses who are hospitalized. The sampling technique is probability sampling with total sampling method. The results of this study are the correlation value / R which is 0.788, the output coefficient of determination (Adjusted R Square) is 0.613, so it can be said that there is an influence of the independent variable on the variable (performance) of 61.3% and the remaining 38.7% is influenced by other factors.